"A SACRED TRUST FOR THE FUTURE": REGULATING INSURANCE, 1800–70. (7th August 2018) - Rawlings, Philip
Abstract: The history of commercial law has often been written as if it were merely a product of the common law, disregarding the role played by legislation. The principal exception to this has been work on company law. Until recently, the prevailing view has been that the Companies Acts 1844–62 represented the triumph of the free market and the expulsion of the state from business. But, although these laws did make incorporation easier and granted companies privileges, what this view ignores is that they also imposed regulation, such as obligations to register the company and charges on its assets and to hold shareholder meetings. At the forefront of these legal changes were insurance companies. Yet, in spite of the proliferation of these companies and their role in, for example, the inquiry that led to the 1844 Act, they have been neglected. This may be because, while the successful campaign in 1824 to remove restrictions on access to the marine-insurance market would seem to support the view of legislation driven by free-market ideas, that explanation seems contradicted by the closing of access to the life-assurance market and the imposition of various obligations on life offices in 1870, a time when the liberalisation of company laws seemed at their peak. Neither development can, however, be so easily explained, and both show the effect of fierce divisions within the insurance industry.